2011
DOI: 10.1111/j.1741-4369.2011.00573.x
|View full text |Cite
|
Sign up to set email alerts
|

Greek kindergarten teachers' beliefs and practices in early literacy

Abstract: This work describes a survey conducted in Syros Island in Greece. The intention was to ascertain kindergarten teachers' perceptions about early literacy and the skills and knowledge they consider as important for pre‐school aged children. The participants were all the kindergarten teachers of the island (N = 19) and the data were collected during a workshop where three groups tried to make a conceptual map of ‘literacy’. The results show that, overall, kindergarten teachers adopt a very broad definition of lit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
5
0
1

Year Published

2016
2016
2023
2023

Publication Types

Select...
6
1

Relationship

2
5

Authors

Journals

citations
Cited by 7 publications
(7 citation statements)
references
References 17 publications
1
5
0
1
Order By: Relevance
“…In line with international research data (see, for example, Ackesjö, 2013; Alatalo et al, 2016Alatalo et al, , 2017Djonov et al, 2018;Dunlop & Fabian, 2006;De Silva Joyce & Feez, 2016;Koustourakis, 2014;Sivropoulou & Vrinioti, 2009;Stellakis, 2012;Xefteri, 2017), kindergarten and primary school teachers make suggestions for a better communication framework (discussion, dialogue, information, joint education and training) and the establishment of a common course of action (common goals, common strands of work between the two levels) at least for the last months of pre-primary and first months of primary school. There is also an important but expected contradiction in their responses, with kindergarten teachers wanting "first grade to move closer to the pre-primary school, in relation to the design of the space, the stimuli, the classroom layout" and teachers wanting "the education and systematic training of the pre-primary school teachers on the teaching syllabus of the primary school, in order to better prepare pupils for the first grade".…”
Section: Findings' Correlation With International Research Datasupporting
confidence: 72%
See 1 more Smart Citation
“…In line with international research data (see, for example, Ackesjö, 2013; Alatalo et al, 2016Alatalo et al, , 2017Djonov et al, 2018;Dunlop & Fabian, 2006;De Silva Joyce & Feez, 2016;Koustourakis, 2014;Sivropoulou & Vrinioti, 2009;Stellakis, 2012;Xefteri, 2017), kindergarten and primary school teachers make suggestions for a better communication framework (discussion, dialogue, information, joint education and training) and the establishment of a common course of action (common goals, common strands of work between the two levels) at least for the last months of pre-primary and first months of primary school. There is also an important but expected contradiction in their responses, with kindergarten teachers wanting "first grade to move closer to the pre-primary school, in relation to the design of the space, the stimuli, the classroom layout" and teachers wanting "the education and systematic training of the pre-primary school teachers on the teaching syllabus of the primary school, in order to better prepare pupils for the first grade".…”
Section: Findings' Correlation With International Research Datasupporting
confidence: 72%
“…Research, mostly on an international level, has explored the views of teachers of preprimary and early primary school (first-grade) regarding the teaching of language (Cook, 2012;Guo, Piasta, Justice, & Kaderavek, 2010;Hawken, Johnston, & McDonnell, 2005;Hindman & Wasik, 2008;Kimmy, 2017;Lynch, 2009;Maloch, Flint, Eldridge, Harmon, Loven, Fine, & Martinez, 2003;Õun, Ugaste, Tuul, & Niglas, 2010;Reutzel, 2015;Sak, Tantekin-Erden, & Morrison, 2016;Sandvik, van Daal, & Ader, 2013;Shaughnessy & Sanger, 2005). In Greece, research focusing on the study of curricula and the perceptions of first-grade primary school teachers of their teaching approaches for language and pre-primary school teachers for literacy hardly exists (Stellakis, 2012;Tafa, Manolitsis, & Fasoulaki, 2011). Moreover, no Greek research has been found concerning the perceptions of first-grade primary school teachers and pre-primary school teachers about the integration of the two curricula, as well as their interrelations.…”
Section: The Current Studymentioning
confidence: 99%
“…We should note that kindergarten education in Greece obligatorily lasts 2 years (4 year olds through age six), and that all the children that have participated in the current study attended their second year. Preschool education in Greece insists on the importance of phonics instruction and grapho‐phonemic correspondences, since direct instruction on letter knowledge and phonological awareness is mandated by the national kindergarten curricula (Manolitsis et al, 2011 ; Stellakis, 2012 ). By age six, children in Greece are expected to have acquired all grapheme‐phoneme correspondences and other letter combination patterns, such as digraphs.…”
Section: Methodsmentioning
confidence: 99%
“…This understanding, in combination with the literature's claim that "the construct of academic language must be viewed as another linguistic register, no more complex or more difficult to acquire than any other register" (Shiel et al, 2012: 196), we hope will lead them to direct their efforts in helping all children succeed in school by exploiting everyone's abilities and skills. Finally, we anticipate that our survey will give rise to the educational authorities to realize the urgent need of providing in-service kindergarten teachers specialized educational programs about early literacy development (Stellakis, 2012), in order to support them in their effort to strengthen children's emergent literacy and preparation for their entrance in school.…”
Section: Conclusion and Discussionmentioning
confidence: 99%